Sorption of Ni2+ Ions by Anion Exchangers based on Epichlorohydrin Oligomers and 4-Vinylpyridine (Global Journal of Science Frontier Research, 2014)
The new anion exchange resin (OECH-VP) was synthesized by polycondensation of oligomer epichlorohydrin (OECH) and 4-vinylpyridine (VP), the static exchange capacity (SEC) of which is equal to 6.75 mg-equiv g -1 in 0.1 M HCI solution and the sorption of Ni 2+ ions were studied. The influence of the concentration and pH of the Nickel (II) sulfate heptahydrate solutions, contact time on the sorption activity of new anion exchangers (ECHO-VP) to nickel ions were studied. Structure of the surface anionite was studied by electronic microscopy method.
Keywords: anion exchange; OECH-VP; SEC; microscopy method